Municípios de pequeno porte do sudeste brasileiro: dinâmica migratória e aspectos econômicos - Nayhara Freitas Martins Gomes (2019)
The main objective of this doctoral thesis is to analyze how the migratory movements of the last 30 years have impacted the small municipalities of the Brazilian Southeastern in demographic and economic terms. The results of the research are synthesized in four chapters preceded by an introductory text and concled with a brief conclusion. The first chapter consists in the theoretical review of approaches to "migratory theories", the "densification of the Brazilian urban network", and especially to that of the Southeast, to "productive restructuring" and reflections on "small municipalities". In the second chapter a spatial taxonomy of small municipalities in southeastearn Brazil is developed, based on the demographic dynamics according to census data of 1991, 2000 and 2010. This analysis allowed the identification of Dynamic, Semi-Stagnated and Debilitated subspaces. The third chapter analyzes the migratory dynamics in the area of the small municipalities and their territorial configurations, allowing to verify the conformation of new nuclei of population attraction. The fourth chapter deals with the economic aspects of the small municipalities of the Southeast, correlated with the migrant labor force, in order to point out new trends in the reordering economic activities in these localities, in addition to reflecting on the diversification of these productive practices. The results demonstrate the strengthening of subspaces composed of small municipalities that participate in the population distribution of the Southeast. The set of four chapters intends to offer a theoretical and methodological contribution on the regional organization of the southeastern Brazil, having as reference the migratory dynamics and economic aspects of the small municipalities.